GWAS and polygenic risk score of severe COVID-19 in Eastern Europe - Kovalenko, Elena; Shaheen, Layal; Vergasova, Ekaterina; Kamelin, Alexey; Rubinova, Valerya; Kharitonov, Dmitry; Kim, Anna; Plotnikov, Nikolay; Elmuratov, Artem; Borovkova, Natalia; Storozheva, Maya; Solonin, Sergey; et al. (Frontiers in Medicine, 2024)
Background: COVID-19 disease has been confirmed more than 772 million times and almost 7 million people have died so far. The severe course of COVID-19 is thought to be preventable with appropriate treatment, but thorough research of the genetic nature of the COVID-19 pathogenesis is needed for its effectiveness. Methods: We performed a genome-wide association study (GWAS) on 7124 people (6400 controls, who had survived COVID-19 without a severe course; 724 cases -patients with severe COVID-19). The inclusion criteria were ARDS (acute respiratory distress syndrome), ARF (acute respiratory failure) requiring respiratory support or CT scans typical of severe COVID-19 infection without any competing diseases. We also trained a polygenic risk score (PRS) model to detect individuals in high-risk group. Results: We identified 2 genome-wide significant loci (p-value <5x10 -8 ) and one locus with approximately genome-wide significance (p-value = 5.92x10 -8 -6.15x10 -8 ). The most genome-wide significant variants were located in the LZTFL1 gene, which was mentioned in several previous GWAS studies. Our PRS model results indicated that people who are in a top-10% group of PRS had twice higher risk of severe course of the disease than those who have median risk (odds ratio, OR = 2.18 [1.66, 2.86], p-value = 8.9x10 -9 ).Conclusions: We performed one of the largest studies of genetics of severe course of COVID-19 on the Eastern European cohort to date. Our results are in concordance with previous research and will guide further epidemiologic studies on host genetics as well as on the development of appropriate treatment.